The Structure of costs and income of broiler chicken farming in different partnership patterns in Sukabumi Regency, West Java, Indonesia - Ujang Sehabudin; Arief Daryanto; Bonar M. Sinaga; Atien Priyanti (Faculty of Animal Science, Universitas Brawijaya, 2022)
In Indonesia, poultry farmers are faced with increasing input prices, especially feed prices, even though the feed is the largest component of broiler chicken production costs, while on the other hand broiler chicken prices fluctuate. This research aimed to analyze cost structure, cost unit, and income broiler chicken on different partnership patterns (PIR and Makloon patterns). The research location is in Sukabumi Regency, which is one of the centers for broiler chicken farming in West Java Province, after Bogor and Ciamis Regencies. The number of respondents was selected based on the partnership pattern, each of which was 130 units using the PIR pattern and 116 units using the Makloon pattern. The results showed that feed costs were the largest of the broiler chicken production costs in the two patterns, respectively 66.64 % in the PIR and 66.08 % in the Makloon pattern. The second biggest production cost is DOC, 26.10 % on the PIR pattern and 25.51 % on the Maklon pattern. The costs of main inputs are more than 90 % of the total production costs, while the operational costs of farmers are less than 10%. Labor costs are the largest costs incurred by farmers. The operational costs incurred by farmers on the PIR pattern are lower than the Makloon pattern, but the fixed costs are the opposite. Although the cost unit (average costs) of broiler chicken farming with the PIR pattern is higher than the Makloon pattern, but the income for the PIR pattern is higher than the PIR pattern. The difference between the total costs of the PIR pattern and the Makloon pattern is 4.40 %, while the difference in total income is 146.59%.